Online instructional design in the new world: Beyond Gagné, Briggs and Wager - Mary Wilson (Adult Education Research Conference, 2018)
MOOCs, Open Access, Badges... all these new technologies should provide a golden age for adult education online. Instead, profoundly traditional models of instructional design impose restrictions.
Keywords: distance education; adult education theory; online education